Optimizing shallot plant growth and plant nutrient through site-specific fertilizer dose evaluation - Solagracya, Jogy Hendro Pratama; Hanum, Hamidah; Sarifuddin (Indonesian Journal of Agricultural Research, 2025)
Shallots are a prominent horticultural commodity significantly influencing national inflation. In the West Aceh region, production of shallot was reduced cause of land degradation (low nutrient availability) that can be achieved by optimizing the application of N, P, K fertilizers and manure. This study aims to identify the optimal doses of fertilizers for shallot production, was conducted from July to September 2023 in Langung Village, West Aceh Regency, Aceh Province, using a Factorial Randomized Block Design. The first factor was the dosage levels of N, P, and K fertilizers (50%, 100%, 150%, and 200% of the Ministry of Agriculture's recommended doses: 150 kg/ha Urea, 150 kg/ha ZA, 185 kg/ha SP-36, and 100 kg/ha KCL), and the second factor was manure application rates (0 ton/ha, 15 ton/ha, and 30 ton/ha), with three replications. The results indicated that the optimal doses of N, P, K, and manure fertilizers for shallot production were found in the P3K2 treatment: 225 kg/ha Urea, 225 kg/ha ZA, 277.5 kg/ha SP-36, 150 kg/ha KCl, and 30 tons/ha manure with plant height at 8 Week after planting (WAP) 32.52 cm, bulb diameters 22.51mm, nutrient content of nitrogen 22.51, nutrient content of phosporus 0.21 and nutrient content of kalium 1.42.